KNOWLEDGE LEVEL OF REAL ESTATE HIBAH IN THE ISLAMIC ESTATE PLANNING - Mohd Musa Bin Sarip; Aminuddin Bin Adnan; Mohd Mustaffa Bin Jusoh (Journal of Islamic, Social, Economics and Development, 2017)
Real estate hibah are specific grant instruments to property assets. In contrast toother assets, its application involves the provisions of the National Land Code. Property typeassets are the largest component of frozen assets reported at RM 60 billion in 2016. Thepurpose of this study is to identify the knowledge level of real estate hibah within the Muslimcommunity. A total of 110 questionnaires have been collected from respondents in the districtof Hulu Langat, Selangor by using the purposive sampling. The data were analysed usingdescriptive and min score analysis. Data analysis found that the level knowledge level of realestate hibah among Muslims is high